The role of cytokines in acute myeloid leukemia: A systematic review - Kupsa, Tomas; Milos Horacek, Jan; Jebavy, Ladislav (Biomedical papers, 2012)
Background: Acute myeloid leukemia (AML) shows a high degree of heterogeneity owing to a variety of mutations and the mechanisms of leukemogenesis. This heterogeneity is often not reflected in standard treatment approaches which while providing predictable outcomes in the majority of patients fail in particular cases even with high-dose multiagent chemotherapy regimens. Further, the unselective effect of chemotherapy leads to high treatment-related toxicity and the enormous risk of infection during prolonged pancytopenia, preventing further dose escalation.Objectives: Cytokines play a role in leukemogenesis, AML cell persistence and treatment outcome. In this review we highlight cytokine dependent mechanisms essential for AML cell survival and the role of single cytokines in leukemogenesis and allogeneic transplantation-related phenomena. Cytokine-related mechanisms of leukemogenesis, AML cell persistence and resistance to chemotherapy are complex. Modulation of the cytokine network can disrupt signalling pathway activation and overcome the high resistance to treatment. It may also increase the selectivity of AML treatment, reduce the overall treatment-related toxicity and improve outcomes of AML treatment in all age groups of patients.Conclusions: This review provides a deeper insight into these processes with focus on the most vulnerable step. Special attention is paid to the possibility of selective influence on defined cell populations for therapeutic target. We believe that modulating cytokine-dependent processes in AML is an approach that could be included in standard chemotherapeutic regimens for improving overall treatment outcome.
Keywords: AML; cytokines; leukemogenesis; prognosis; treatment approaches